Pre-notched and corroded low cycle fatigue behaviour of a nickel based alloy for disc rotor applications. (December 2017) - Dowd, M.; Perkins, K.M.; Child, D.J.
Highlights: A mechanism change occurs where corrosion becomes localised to the grain boundaries. The inward migration of sulphide particles serves to propagate the mechanism. Oxides formed in the wake of sulphide particles fractures around segments of grains. Grain dropout leads to a metal loss that contributes to reduced fatigue properties. Abstract: Currently there is doubt surrounding the suitability of chemically-induced stress independent pre-conditioning of specimens to simulate turbine corrosion prior to fatigue testing. The thick oxide scales developed using such techniques can lead to net section loss and typically a lack of grain boundary sulphide attack seen in components that experience stress. An alternative approach to a corrosion-fatigue test scenario is suggested by micro-notching fatigue specimens prior to low salt flux corrosion to form grain boundary sulphide particles within channel-like features akin to stress assisted morphologies. On fatigue testing, a trend was identified where a change of mechanism was observed. The grain boundary oxide likely formed in the wake of freshly precipitated sulphide particles fractures around segments of grains leading to a metal loss that contributes to a significant reduction in fatigue properties.